Peran Pemerintah dalam Melakukan Pengawasan di Sektor Perikanan Indonesia (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
The fisheries sector plays a strategic role in Indonesia's national economic development due to its significant contribution to meeting food needs, creating jobs, and earning foreign exchange. However, this sector still faces various serious challenges, such as Illegal, Unreported, and Unregulated (IUU) Fishing practices, excessive exploitation of marine resources, degradation of aquatic ecosystems, and weak compliance with applicable legal provisions. These problems not only impact the sustainability of fisheries resources but also threaten the economic sustainability of coastal communities. This study aims to analyze the government's role in overseeing the fisheries sector in Indonesia, which includes regulatory and institutional aspects, and the implementation of supervision in the field. The research method used is a normative juridical approach through a review of relevant laws and regulations, including Law Number 31 of 2004 concerning Fisheries as amended by Law Number 45 of 2009, and other derivative regulations. The analysis also considers the role of supervisory institutions such as the Ministry of Maritime Affairs and Fisheries (KKP), the Indonesian Navy (TNI AL), and law enforcement officials in preventing and prosecuting violations in this sector. The research findings indicate that the government plays a strategic role in establishing policies, establishing oversight institutions, providing monitoring facilities and infrastructure, and taking legal action against violators. However, oversight effectiveness is still suboptimal due to limited human resources, monitoring technology, inter-agency coordination, and low legal awareness among fisheries business actors. Therefore, strengthening an integrated oversight system, increasing the capacity of officials, utilizing information and satellite technology, and consistent law enforcement are necessary. These steps are expected to ensure sustainable management of Indonesia's fisheries sector, protect marine resources, and support national economic growth.